1985
DOI: 10.1159/000242195
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Zinc and Copper in Maternal and Cord Blood at Delivery

Abstract: For 17 normal births, the concentrations of trace metals (zinc and copper) and related metalloenzymes, i.e., carbonic anhydrase isoenzymes (CA-I and CA-II) and Cu2Zn2 superoxide dismutase (SOD1) were simultaneously determined in maternal and cord blood at delivery. Eleven healthy nonpregnant women served as controls. CA-I concentration in maternal erythrocytes was higher than in controls (p < 0.05), whereas the concentrations of both CA isoenzymes in cord erythrocytes were in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
2

Year Published

1987
1987
2000
2000

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
4
4
2
Order By: Relevance
“…Since SOD | concentration in the NST was higher than in controls, the NST total copper con centration in erythrocytes appeared to be higher as compared to the control value. In contrast, it has been demonstrated that total copper concentration in maternal erythro cytes immediately after delivery (which cor responds to phase 4 in our study) is signifi cantly lower than in nonpregnant women although the SOD] concentration does not vary substantially [6,18], In the present study, however, no difference was noted be tween them. This disparity remains to be elucidated since the results on plasma copper concentration are in good agreement with those of previous studies [2,6,18], Total plasma zinc concentration did not decrease significantly in the NST, there being a nearly 10% decline below the control values.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Since SOD | concentration in the NST was higher than in controls, the NST total copper con centration in erythrocytes appeared to be higher as compared to the control value. In contrast, it has been demonstrated that total copper concentration in maternal erythro cytes immediately after delivery (which cor responds to phase 4 in our study) is signifi cantly lower than in nonpregnant women although the SOD] concentration does not vary substantially [6,18], In the present study, however, no difference was noted be tween them. This disparity remains to be elucidated since the results on plasma copper concentration are in good agreement with those of previous studies [2,6,18], Total plasma zinc concentration did not decrease significantly in the NST, there being a nearly 10% decline below the control values.…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast, it has been demonstrated that total copper concentration in maternal erythro cytes immediately after delivery (which cor responds to phase 4 in our study) is signifi cantly lower than in nonpregnant women although the SOD] concentration does not vary substantially [6,18], In the present study, however, no difference was noted be tween them. This disparity remains to be elucidated since the results on plasma copper concentration are in good agreement with those of previous studies [2,6,18], Total plasma zinc concentration did not decrease significantly in the NST, there being a nearly 10% decline below the control values. This result was inconsistent with those of many studies in which the mean zinc concentra tion in maternal plasma/serum is apparently lower than in normal nonpregnant individu als [1][2][3][4], The discrepancy is probably due to the fact that there was a rising tendency in aj-MG-bound zinc concentration in the NST.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Cord zinc erythrocyte concentrations were about one fourth the maternal values, as previously observed [11,27], probably due to lower concentrations of carbonic anhydrase isoenzymes in cord compared to maternal erythrocytes [11], In contrast, metallothionein concentrations were similar in maternal and cord erythrocytes in all groups but only in cord, erythrocyte metallothionein and zinc levels tended to be correlated, suggesting some difference in maternal and cord regula tion of erythrocyte metallothionein. Pregnant women at delivery were shown to have slight 90 Biol Neonate 1997:72:84-93…”
Section: Effect O F Maternal Serum Zinc Levelssupporting
confidence: 70%
“…Most studies on maternal-fetal transfer of zinc have related maternal and cord serum zinc, observing either a significant correlation [6,7] or no correlation [8][9][10], A few studies have measured maternal serum zinc in rela tion to other maternal indices of zinc status [11][12][13] and/or to placental zinc [12,14] and cord serum components [4] in normal preg nancies, but the physiological significance of variations in serum zinc in healthy pregnant women is still unclear.…”
Section: Introductionmentioning
confidence: 99%